Defining a Healthy Organisation in Primary Care: A Qualitative Interview Study. Issue 2 (2nd April 2020) - Williams, Stephen P.; Panigyraki, Artemis; Purkayastha, Sanjay; Chaturvedi, Sankalp; Benn, Jonathan; Darzi, Ara
Abstract: This study aimed to qualitatively develop a conceptual framework for organizational health, within the setting of GP practices in the UK, through a qualitative interview study utilizing aspects from grounded theory. Data saturation was reached after 33 interviews revealing six themes: Strategy, Resources, Leadership, Staff Wellbeing, Capacity for change and Ways of working . The structure of each theme is discussed in detail. By unpicking the elements of organizational health in GP practices in this way, we hope to shift focus from considering down-stream clinical outcomes in isolation to practices taking a more long-term view centered around fostering ongoing high performance.